Exploring Perspectives of Disaster Survivors on Islamic-Based Nurses' Disaster Response Competencies: A Study from Disaster Front Area - Husna, Cut; Kamil, Hajjul; Yahya, Mustanir; Tahlil, Teuku (Journal of Liaquat University of Medical & Health Sciences, 2024)
Objective: The study aims to explore the perspective of disaster survivors on Islamic-based nurses' competencies in response to disasters, principally in handling psychological, psychosocial, and spiritual conditions. Methodology: A qualitative study with a descriptive phenomenology design was conducted. The data collection using a focus group discussion with five interview guides for nine disaster survivors was involved in this study. The data was evaluated through thematic analysis using sub-themes and themes, followed by qualitative steps. Results: The study identified three themes related to disaster survivors' perspective: 1) Perception of disaster: tests and punishments, 2) Nurses' competencies: skills and attitude, and 3) Integrating Islamic values: spiritual support and motivation. Conclusion: The study indicated that the Islamic-based nurses' disaster response competencies identified an essential role in dealing with psychological, psychosocial, and spiritual problems among disaster survivors from the Islamic perspective.